Legitimizing Rhetorics: Jewish “Heresy” in Early Modern Italy - Bernard Dov Cooperman (Etudes Epistémè)
Granted the weakness of Jewish institutions for social control, arguments for freedom of thought and criticism of authority could flourish relatively unimpeded within the community. Communities did use decrees of excommunication to expel individuals for various types of actions—especially those related to economic competition and taxation or crossing halakhic marital rules and other such malfeasance. But when it came to matters of belief and doctrine, demands to “excommunicate” deviants seem to have remained largely rhetorical, at least until the seventeenth century. What is remarkable is not only the open rejection of any claims to universal authority but the justification for freedom of thought, the importance of individual rational ethics in self-perfection, the rejection of blind credulousness, and the use of historical critical methods to establish the authentic Jewish tradition.